Fe(III)-Catalyzed Bicyclization of Yne-Allenones With Indoles for the Atom-Economic Synthesis of 3-Indolyl Cyclobutarenes - Li, Heng; Hao, Wen-Juan; Li, Guigen; Tu, Shu-Jiang; Jiang, Bo (Frontiers in Chemistry, 2018)
A new Fe(III)-catalyzed bicyclization reaction of yne-allenones with indoles has been established, enabling the direct construction of cyclobuta[a]naphthalen-4-ols with an all-carbon quaternary center in good to excellent yields. This reaction was performed by using low-cost FeCl3 as the catalyst and EtOH as the environmentally benign solvent, providing a green protocol for constructing cyclobutarene framework with a high degree of atom economy and functional group compatibility. The reaction mechanism was proposed through a [2 + 2] cycloaddition/1,6-conjugate addition cascade